Uz knjigu prof. dr. Ive Komšića / Accompaniment to a Book by Prof. Dr. Ivo Komšić - Lavić, Senadin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
This text is a review of a book Tuđmanov haški profil. Udruženi zločinački poduhvat na BiH (Tuđman's Hague Profile - Joint Criminal Enterprise in BiH) by Prof. Dr. Ivo Komšić, Zagreb, Sarajevo: Sinopsis, 2021.